1992
DOI: 10.1007/bf02535583
|View full text |Cite
|
Sign up to set email alerts
|

Nonessential fatty acids in formula fat blends influence essential fatty acid metabolism and composition in plasma and organ lipid classes in piglets

Abstract: The n-6 and n-3 fatty acid status of developing organs is the cumulative result of the diet lipid composition and many complex events of lipid metabolism. Little information is available, however, on the potential effects of the saturated fatty acid chain length (8:0-16:0) or oleic acid (18:1) content of the diet on the subsequent metabolism of the essential fatty acids 18:2n-6 and 18:3n-3 and their elongated/desaturated products. The effects of feeding piglets formulas with fat blends containing either coconu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The different metabolic pathways of these fatty acids may influence the content of other saturated fatty acids in plasma. In fact, a study done in piglets showed that a diet containing 12:0 and 14:0 lead to a higher percentage of longer saturated fatty acids than a diet containing 8:0 and 10:0 as a medium chain fatty acids (41).…”
Section: Discussionmentioning
confidence: 99%
“…The different metabolic pathways of these fatty acids may influence the content of other saturated fatty acids in plasma. In fact, a study done in piglets showed that a diet containing 12:0 and 14:0 lead to a higher percentage of longer saturated fatty acids than a diet containing 8:0 and 10:0 as a medium chain fatty acids (41).…”
Section: Discussionmentioning
confidence: 99%
“…The portal-venous transport of 8:0, 10:0, and 12:0, followed by rapid carnitine-independent oxidation in liver, and the low activity of acyltransferases with medium-chain fatty acids (24,25,30,31) are well known. Previous studies have suggested that preferential oxidation of 8:0-12:0 in animals fed diets with 8:0-12:0 rather than 16:0 as the source of saturated fat may result in higher availability of dietary 18:1 and 18:2n-6 for storage in growing tissue lipids (32). The results of this report, which show higher 18:1, and to a smaller extent higher 18:2n-6, in liver triglycerides of piglets fed the formula with MCT rather than oils with 16:0 as the source of saturated fat, are consistent with this.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of MCT is associated with profound changes in plasma fatty acid composition (8,9), but the effects of MCT on essential fatty acid and LCP status are controversial. Wall et al (10) found significantly lower tissue levels of arachidonic acid in new-born piglets fed infant formulas containing MCT than in piglets fed formulas containing coconut oil (12:0 ϩ 14:0). In premature infants, an interference of MCT on LCP metabolism was suggested by Carnielli et al (9), who reported no effect on 20:4n-6 concentrations but a decrease in plasma phospholipid 22:6n-3 concentrations after MCT feeding.…”
mentioning
confidence: 98%